Regioselective and diastereodivergent organocatalytic asymmetric vinylogous Michael addition. Issue 17 (24th June 2021) - Zou, Chuncheng; Lv, Yanting; Lu, Min; Li, Xin; Zhang, Lei; Yang, Lei; Liu, Zhen; Ke, Yanxiong; Song, Gonghua; Ye, Jinxing
Abstract : Regioselective and diastereodivergent γ-position asymmetric vinylogous Michael addition (AVMA) of cyclohex-2-enones to nitroalkenes and γ′-AVMA between cyclohex-3-enones and nitroalkenes. Abstract : Regioselective and diastereodivergent asymmetric vinylogous Michael addition (AVMA) between β-substituted-cyclohexenones and nitroalkenes via dienamine activation under complementary chiral aminocatalysts was reported. γ-Regioselective AVMA of β-alkyl-cyclohex-2-enones via a linear exo -dienamine mechanism and γ′-regioselective functionalization of β-substituted-cyclohex-3-enones via a cyclic extended endo -dienamine mechanism were reported in satisfactory yields with high enantio- and diastereoselectivities. DFT calculations reasonably explained that the diastereoselectivity of the reactions at the γ- and γ′-positions is achieved by regulating the orientation of the nitroalkenes through the hydrogen-bonding interaction and steric hindrance effect. Furthermore, the four different configurations of the γ- and γ′-adducts were diversified to the corresponding enantioenriched spirocyclic ketones and cis -2-decalones with multiple chiral centers.